Same time next summer ebook - Monaghan, Annabel (2023)
“Bursting with the magic of first love, it’s everything I want in a summer romance.” —Carley Fortune, #1 New York Times bestselling author of EVERY SUMMER AFTER Named a Best Book of Summer by Real Simple • Reader’s Digest • Country Living • The Skimm • BookBub • GoodReads Beach Rules: Do take long walks on the sand. Do put an umbrella in every cocktail. Do NOT run into your first love.     Sam’s life is on track. She has the perfect doctor fiancé, Jack (his strict routines are a good thing, really), a great job in Manhattan (unless they fire her), and is about to tour a wedding venue near her family’s Long Island beach house. Everything should go to plan, yet the minute she arrives, Sam senses something is off. Wyatt is here. Her Wyatt. But there’s no reason for a thirty-year-old engaged woman to feel panicked around the guy who broke her heart when she was seventeen. Right?      Yet being back at this beach, hearing notes from Wyatt’s guitar float across the night air from next door as if no time has passed—Sam’s memories come flooding back: the feel of Wyatt’s skin on hers, their nights in the treehouse, and the truth behind their split. Sam remembers who she used to be, and as Wyatt reenters her life their connection is as undeniable as it always was. She will have to make a choice.